Tinidazole-Induced Fixed Drug Eruption: A Case Report - Kumar Sarkar, Manuj; Mishra, Rishu; Pandya, Parth; Bansal, Aastha; Singh Bajhaiya, Babeena; Mithun, Mithun (International Journal of Medical Research and Review, 2015)
FDE is characterized by onset of oval or round erythematous macule on the mucosa or skin. Patients may have itching and burning sensation. 22 years old married female presented with complaining of burning sensation and ulceration in lower lip and erythematous well-defined macule on muco-cutaneous junction of vagina for last two days following intake of Tinidazole 400 mg twice daily for 1 day. FDE though not fatal, can cause cosmetic disfigurement. Fixed drug eruption in genital region is a matter of apprehension. The exact mechanism of FDE is unknown.